Three-Port versus Four-Port Laparoscopic Cholecystectomy: A Randomized Controlled Trial - Koirala, Rabin; Gurung, TM; Rajbhandari, A; Rai, P (Nepal Medical College Journal, 2019)
Laparoscopic cholecystectomy (LC) is one of the most common surgery performed and is traditionally performed using four ports. With the aim of improving patient’s comfort, port numbers have been reduced to single port. But feasibility and the extra expense that comes with single and double port LC has made them less attractive. Three port LC can be a safe alternative to four port LC, and various research has shown its safety. This study compares the three port LC with the traditional four port LC with the objective of assessing feasibility and benefit of the decreased port number. We evaluated 217 patients who were randomly allocated for three port and four port LC. Both the groups were compared for operative time, assessment of postoperative pain, days of hospital stay and postoperative recovery time after discharge. The parameters were compared using Statistical Package for the Social Sciences (SPSS) version 16. Among 217 patients, 123 underwent three port LC and 94 underwent four port LC. The larger number were females (79.7%), and with comparable age group of patients. Rate of conversion to open cholecystectomy, postoperative pain scale, analgesic requirement, average hospital stay and port site infection rates were comparable in both groups of patients. The average time taken for operation was less in three port LC than the four port LC but this was not statistically significant. There is no significant difference between 3 port and 4 port LC in terms of time required for the surgery, conversion rate, complication and duration of hospital stay.